The Relationship Between Knowledge and Computer Vision Syndrome Prevention Behavior in Computer User Employees at Setco Group Pekanbaru - Dasrinal Dasrinal (The International Science of Health Journal, 2024)
Background: Computer Vision Syndrome (CVS) refers to a group of eye and vision-related problems that result from prolonged computer use. The prevalence of CVS among office workers varies but is notably high. Studies indicate that the prevalence of CVS symptoms can range from 50% to 90% among regular computer users. CVS occurs due to poor computer use behaviors such as incorrect sitting position and lack of breaks while using the computer. Bad behavior in using computers is influenced by poor knowledge in using computers. Based on an initial survey, 70% of employees experienced CVS. Objective: To determine the relationship between knowledge and CVS prevention behavior of computer user employees at Setco Group Pekanbaru. Methods: Observational analytic research with cross sectional design, data collection technique used total sampling with a sample size of 122 respondents. Data analysis was performed bivariate using the Spearman correlation test. Results: Based on the Spearman correlation test on knowledge of CVS prevention behavior, it was found that there was a relationship between CVS prevention knowledge and CVS prevention behavior with a positive direction and weak correlation strength (p-value 0.011) and r 0.229. Conclusion: There is a relationship between knowledge and CVS prevention behavior in employees who use computers.